Tetherin is a key effector of the antiretroviral activity of type I interferon in vitro and in vivo - Liberatore, Rachel A. (National Academy of Sciences, 2011)
Tetherin (Bst-2 CD317) is a cell-surface protein whose expression is induced by IFNα. Although tetherin expression causes the retention of retrovirus particles on the surface of infected cells, it is not known whether tetherin inhibits retroviral replication or pathogenesis in vivo. Mutation of tetherin antagonists often has little effect on retroviral replication in vitro, and, although tetherin can reduce the yield of extracellular viral particles, some studies suggest that tetherin actually enhances direct cell-to-cell viral transmission. We generated tetherin-deficient mice to determine the effect of this protein on murine retrovirus replication and pathogenesis. We find that tetherin markedly inhibits the replication of Moloney murine leukemia virus (Mo-MLV) and is required for the antiretroviral activity of IFNα to be fully manifested in vitro. Surprisingly, Mo-MLV replication and disease progression was not significantly different in WT and tetherin-deficient mice, but this finding was explained by the fact that Mo-MLV infection did not induce detectable tetherin expression on candidate target cells in vivo. Indeed, IFNα induction was required to reveal the anti–Mo-MLV activity of tetherin in vivo. Moreover, LP-BM5, an MLV strain that has been demonstrated to induce immune activation and IFNα expression, achieved higher levels of viremia and induced exaggerated pathology in tetherin-deficient mice. These data indicate that tetherin is a bona fide antiviral protein and can reduce retroviral replication and disease in vivo.